The immunization programme that saved millions of lives (The World Health Organization, 2014)
What started as an ambitious effort to tackle six vaccine-preventable diseases has become one of the world's most successful public health programmes. This month the Expanded Programme on Immunization marks its 40 years. Michael Reid and Fiona Fleck report.